Global environmental implications of atmospheric methane removal through chlorine-mediated chemistry-climate interactions - Li, Qinyi (2023)
Atmospheric methane is both a potent greenhouse gas and photochemically active, with approximately equal anthropogenic and natural sources. The addition of chlorine to the atmosphere has been proposed to mitigate global warming through methane reduction by increasing its chemical loss. However, the potential environmental impacts of such climate mitigation remainunexplored. Here, sensitivity studies are conducted to evaluate the possible effects of increasing reactive chlorine emissions on the methane budget, atmospheric composition and radiative forcing. Because of non-linear chemistry, in order to achieve a reduction in methane burden (instead of anincrease), the chlorine atom burden needs to be a minimum of three times the estimated present-day burden. If the methane removal target is set to 20%, 45%, or 70% less global methane by 2050 compared to the levels in the Representative Concentration Pathway 8.5 scenario (RCP8.5), our modeling results suggest that additional chlorine ﬂuxes of 630, 1250, and 1880 Tg Cl/year, respectively, are needed. The results show that increasing chlorine emissions also induces signiﬁcant changes in other important climate forcers. Remarkably, the tropospheric ozone decrease is large enough that the magnitude of radiative forcing decrease is similar to that of methane. Adding 630, 1250, and 1880 Tg Cl/year to the RCP8.5 scenario, chosen to have the mostconsistent current-day trends of methane, will decrease the surface temperature by 0.2, 0.4, and 0.6 °C by 2050, respectively. The quantity and method in which the chlorine is added, its interactions with climate pathways, and the potential environmental impacts on air quality and ocean acidity, must be carefully considered before any action is taken.